Drivers and inhibitors adopting renewable energy: an empirical study in Malaysia - Zahari A.R.; Esa E. (Emerald Group Holdings Ltd., 2023)
Housing; Consumer decision making; Design/methodology/approach; Malaysia; Partial least square (PLS); Renewable energies; Renewable energy strategies; Theoretical framework; Use of renewable energies; Decision making